2022
DOI: 10.1186/s12888-022-03704-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiovascular metabolic risk factor measurements with psychiatric readmission among in-hospital patients with severe mental illness: a retrospective study

Abstract: Background Patients with severe mental illness (SMI) and comorbid physical conditions were often associated with higher risks of mortality and hospital readmission. In this study, we aim to examine the association of cardiovascular metabolic risk factor measurements with risks of psychiatric readmissions among in-hospital patients with severe mental illness (SMI). Methods We collected the longitudinal information of laboratory investigations, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Considering associations between hypertriglyceridemia, central obesity, hyperglycemia, and readmission, it was not surprising to find an increased risk of readmission in non-smoking patients with metabolic syndrome. Thus, inpatients with severe mental illness whose metabolic risk factors were poorly monitored had an increased risk of readmission ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering associations between hypertriglyceridemia, central obesity, hyperglycemia, and readmission, it was not surprising to find an increased risk of readmission in non-smoking patients with metabolic syndrome. Thus, inpatients with severe mental illness whose metabolic risk factors were poorly monitored had an increased risk of readmission ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings should be carefully evaluated due to the small sample size. A recent study found a substantial link between dyslipidemia and acute-phase schizophrenia (61). Thus, more mechanistic studies are needed to better understand the relationship between HDL hypocholesterolemia and readmission in psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“… 17 With higher rates of metabolic syndrome among mood disorders, psychiatric facilities require systemic integration of metabolic and cardiovascular assessment during admission. 18 Evidence from psychiatric readmission rates has shown that poor assessment and monitoring of metabolic risk factors of inpatients increases the likelihood of readmission 19 , 20 within a 28-day period. 21 While evidence is clear that exercise is beneficial in reducing symptomology in depression, anxiety disorders, bipolar disorder, and schizophrenia, 22 the lack of consistent and well-documented metabolic and cardiovascular assessment may reflect missed opportunities to improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 21 While evidence is clear that exercise is beneficial in reducing symptomology in depression, anxiety disorders, bipolar disorder, and schizophrenia, 22 the lack of consistent and well-documented metabolic and cardiovascular assessment may reflect missed opportunities to improve treatment outcomes. 20 The lack of accessible documentation in the hospital file of activity patterns and markers or metabolic health prior to admission, on discharge and post discharge renders it impossible to determine if exercise was beneficial for those that accessed services in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…CVD includes arrhythmia, cardiomyopathy, coronary artery disease, heart attack, heart failure, and stroke (Everson-Rose & Lewis, 2005). It has been established that people with schizophrenia receive less equitable access to care compared to the general population (Crawford et al, 2014;Kisely et al, 2007;Mitchell & Lord, 2010;Osborn et al, 2011), where this suboptimal care often results in increased risk for psychiatric readmissions where CVD risk factors have not been adequately monitored (Tan et al, 2022). Tan and colleagues (2022) found that psychiatric readmissions were 37% more likely for people with poor follow-up care for blood lipid levels and 32% more likely for people with poor follow-up care for hypertension.…”
Section: Understanding Morbidity and Mortality In Schizophreniamentioning
confidence: 99%